2019
DOI: 10.3906/elk-1903-186
|View full text |Cite
|
Sign up to set email alerts
|

GACNN SleepTuneNet: a genetic algorithm designing the convolutional neuralnetwork architecture for optimal classification ofsleep stages from a single EEG channel

Abstract: This study presents a method for designing-by a genetic algorithm, without manual intervention-the feature learning architecture for classification of sleep stages from a single EEG channel, when using a convolutional neural network called GACNN SleepTuneNet. Two EEG electrode positions were selected, namely FP2-F4 and FPz-Cz, from two available datasets. Twenty-five generations were involved in diagnosis without hand-crafted features, to learn the architecture for classification of sleep stages based on AASM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The earlier works [11,16,17,23] confirmed that the combination of DF and HF (DF+HF) will improve the performance of deep-learning system. In this work, the essential HF from the brain MRI slices are mined using the well known methods such as GLCM [3,10,29], Hu [3,10,30] and LBP [31,32]. The GLCM is widely adopted due to its superior performance and the essential GLCM parameters of the MRI slices are extracted from the segmented BT by VGG-UNet.…”
Section: Handcrafted-featuresmentioning
confidence: 99%
“…The earlier works [11,16,17,23] confirmed that the combination of DF and HF (DF+HF) will improve the performance of deep-learning system. In this work, the essential HF from the brain MRI slices are mined using the well known methods such as GLCM [3,10,29], Hu [3,10,30] and LBP [31,32]. The GLCM is widely adopted due to its superior performance and the essential GLCM parameters of the MRI slices are extracted from the segmented BT by VGG-UNet.…”
Section: Handcrafted-featuresmentioning
confidence: 99%